Evaluasi Program Layanan Antar Jemput Pasien dan Jenazah Dalam Aksesibilitas Pelayanan Kesehatan Masyarakat di Kabupaten Karangasem - Candrika, Ni Putu; Yudartha , ⁠I Putu Dharmanu; Wijaya, Komang Adi Sastra (Lenggogeni Data Publishing, 2025)
This study aims to evaluate the Patient and Corpses Pickup Service Program (AJP) in improving the accessibility of health services for the community in Karangasem Regency. The AJP program was launched in response to the geographical and socio-economic challenges faced by underprivileged communities, especially in remote areas that are difficult to reach. The research method used is qualitative with a descriptive approach, involving interviews with key informants from the Health Office and community members who use the service. The results of the study indicate that the AJP program has successfully increased the accessibility of health services for underprivileged communities, with an increase in the number of service users from year to year. However, there are still obstacles in the implementation of the program, such as limited transportation facilities, lack of socialization, and issues in the service usage process. The evaluation is conducted based on six criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. From the evaluation results, it is concluded that although the AJP program is effective in providing services, improvements are still needed in terms of socialization and resource management to ensure that services can be accessed equitably by the entire community. Recommendations include enhancing socialization, optimizing human resources, and increasing facilities and infrastructure to support the smooth operation of the program.